Geology and petrography of the Nagar Parkar Igneous Complex, southeastern Sindh: the Wadhrai body - Jan, M. Qasim; Agheem, M. Hassan; Laghari, Amanullah; Anjum, Suhail (Journal of Himalayan Earth Sciences, 2016)
The Wadhrai igneous body occurs to the north of the Nagar Parkar town. This and other bodies constituting the Nagar Parkar Igneous Complex are an extension of the Malani Igneous Suite of western Rajasthan. The body is occupied by petrographically uniform granite composed of perthite, albitic plagioclase, quartz, and small quantities of biotite, opaque oxide and titanite. The rocks are sparingly porphyritic and contain dykes and veins of microgranite, aplite and quartz; pegmatites are rare and simple. In the southeastern part, the granite is invaded by parallel sheets and swarms of many mafic dykes, and rhyolite sheets. The mafic dykes are porphyritic to aphyric and consist of calcic plagioclase, hornblendic amphibole or clinopyroxene +/- olivine, ilmenite, titanite and a range of secondary minerals. Many of the mafic dykes are strongly altered, some totally, and a few beyond recognition. The rhyolite sheets are sparsely porphyritic, at places banded, and composed of perthite, quartz, albite, sodic amphibole, aegirine-augite, opaque oxide and titanite. The main rhyolite sheet extends for more than 2 km and attains a thickness of 30 m. While the felsic dykes are apparently related to the granite, the mutual relations between the granite, mafic and rhyolite sheets are yet to be deciphered, but the rhyolites may represent melts derived from the crust through underplating by mafic magma. This paper gives detailed petrography of the rocks, together with newly prepared geological maps.